แนวทางการนำยุทธศาสตร์การจัดการศึกษาทางไกลผ่านเทคโนโลยีสารสนเทศไปสู่การปฏิบัติ ของโรงเรียนสังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - ฐิติวัฒนานันท์ นภัสสรณ์; กิจนันทวิวัฒน์ วิรุจ (An Online Journal of Education, 2018)
This research aims to proposed approaches for implementation of Distance learning information technology (DLIT) strategies in schools under the office of the Basic Education Commission, Both quantitative and qualitative methods of research methodology were used, with data collected from school director and teacher who teach student by DLIT in schools under the office of Secondary Area 269 schools and provided qualitative data from interviewing school directors and teacher to suggest approaches for implementation of Distance learning information technology (DLIT) Strategies in schools under the office of the Basic Education Commission The Questionnaire and interviews were used to collect data and analyse by calculating the mean, percentages and PNI modification was used to analysed needs assessment for approaches for implementation. The result of the study revealed that the needs of implementation of Distance learning information technology (DLIT) Strategies in schools under the office of the Basic Education Commission is in the following order 1. Learning process 2. Institutional management within the institution 3. Cooperation in public, private and community 4. Teaching and learning 5. Learning resources and 6.Infrastructure